New ethanol and propylene glycol free gel formulations containing a minoxidil-methyl-β-cyclodextrin complex as promising tools for alopecia treatment. (21st March 2014) - Lopedota, Angela; Cutrignelli, Annalisa; Denora, Nunzio; Laquintana, Valentino; Lopalco, Antonio; Selva, Stefano; Ragni, Lorella; Tongiani, Serena; Franco, Massimo
Abstract: New topical totally aqueous formulations that improve the low water solubility of minoxidil and realize an adequate permeability of drug in the skin are proposed. These formulations are lacking in propylene glycol and alcohol that are the principal irritant ingredients present in minoxidil commercial solutions. In order to enhance poor water solubility of minoxidil randomly methyl-β-cyclodextrin was used, and four hydrogels such as, calcium alginate, sodium alginate, carbopol 934 and hydroxyethylcellulose were utilized to ensure a prolonged time of contact with the scalp. The inclusion complex minoxidil/methyl-β-cyclodextrin with a molar ratio 1:1 was obtained by freeze drying and evaluated by NMR, FT-IR and DSC analysis. An apparent stability constant of formed inclusion complex was calculated by phase solubility diagram and its value was 400 M −1 . The solid inclusion complex was used to prepare gel formulations with similar dose to minoxidil commercial solution. The gels were evaluated for various technological parameters including rheological behavior, in vitro drug release and ex vivo permeation through pig skin. The best performance was observed for the calcium alginate formulation.